Changes in tear protein profile in dogs with keratoconjunctivitis sicca following topical treatment using cyclosporine A - Sussadee, Metita; Rucksaken, Rucksak; Havanapan, Phattara-Orn; Reamtong, Onrapak; Thayananuphat, Aree (Veterinary World, 2021)
Background and Aim: Keratoconjunctivitis sicca (KCS) is a chronic inflammatory ocular disease that occurs in many dog breeds worldwide. This study aimed to investigate the tear protein pattern of healthy dogs, KCS dogs, and KCS dogs after treatment with cyclosporine A (CsA). Materials and Methods: Twenty-eight dogs of any breed were enrolled in the study. The subjects were divided into three groups: Healthy, KCS, and CsA-treated dogs. Tear samples were collected using Schirmer strips. Tear proteins extracted from the strips were analyzed using two-dimensional electrophoresis. For the first dimension, total protein from tears was separated by isoelectric focusing. The second dimension was performed using 12.5% sodium dodecyl sulfate-polyacrylamide gel electrophoresis. The gel images were analyzed and the protein spots of differential expression were manually cut for protein annotation using mass spectrometry. Results: In total, 12 protein spots were excised and subjected to protein identification. Associated with KCS, six protein spots were a downregulated protein, namely, lysozyme. The other six protein spots were upregulated in KCS dogs, consisting of heat shock protein beta-1, protein S100-A12, and keratin type II cytoskeletal 1 and 5. After treatment with CsA for 45 days, the lysozyme protein was still decreasing and the inflammation protein (S100-A12) was not identified. Conclusion: Inflammatory tear proteins and proteins involved in cellular stress were present in KCS dogs and appeared to be reduced in medicated eyes. Treatment with topical CsA in the short term may not improve the activity of antibacterial proteins. Changes in the expression patterns of these four proteins might be useful for disease severity and progression assessment, as well as for exploring a novel method for dry eye management in dogs.